Implementasi High Availability Web Server Menggunakan Metode Web Cluster Dan High Availability Proxy Pada Single Board Computer (Studi Kasus: UD Sendang Putra) - Roisul Setiawan; Bayu Rahayudi; Dany Primanita Kartika Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
UD Sendang Putra is a business engaged in the distribution, sale and service of foodstuffs. Since this business was established, all transaction and administrative activities were carried out manually. In its development UD Sendang Putra has begun to migrate to the information system, but in its development UD Sendang Putra has difficulty implementing the system to the server because the work environment is not suitable for server installations. From this problem a cluster server is created from a single board computer. To increase availability, 4 single board computers are designed using a distributed system method so that the server can serve requests properly. In its development this server was built using 2 Raspberry Zero W for load balancers and servers, which are designed to be able to serve 3 functional requirements and 5 non functional requirements. Functional and non functional testing of the system produces valid values for all requirements. Performance testing stated that the cluster server is ideally used by 110 users because it is still within the safe limit of resource use of 80%. Based on the results of performance testing, the server cluster has an availability level of 98.53% and it can be concluded that the server cluster is feasible to use at UD Sendang Putra.